Large scale soil health restoration the way forward for reversing climate change while enhancing food and nutrition security. - Setboonsarng, Sununtar (Southeast Asia working papers., 2017)
Soil has been overlooked as a natural resource yet it can be an ally in bringing carbon dioxide levels down by functioning as a natural carbon sink. Soil health is also central in feeding a growing global population. Healthy soil increases the adaptive capacity of plants to withstand extreme weather conditions and lessens crop failures. Healthy soil is also essential to fight malnutrition, particularly in rural areas.